2007
DOI: 10.1016/j.jasms.2007.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectra of acyl carrier protein are insensitive to its solution phase conformation

Abstract: Electrospray ionization mass spectrometry (ESI-MS) can be used to monitor conformational changes of proteins in solution based on the charge state distribution (CSD) of the corresponding gas-phase ions, although relatively few studies of acidic proteins have been reported. Here, we have compared the CSD and solution structure of recombinant Vibrio harveyi acyl carrier protein (rACP), a small acidic protein whose secondary and tertiary structure can be manipulated by pH, fatty acylation, and site-directed mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Apo-linL46W displayed a broad CSD of ions from 6 ϩ to 9 ϩ (maximum at 8 ϩ ) in positive ESI mode (Fig. 5C), which is similar to that observed for wild-type V. harveyi ACP (34). CycL46W, on the other hand, produced a sharp, narrow CSD of predominantly 6 ϩ and 7 ϩ ions (Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Apo-linL46W displayed a broad CSD of ions from 6 ϩ to 9 ϩ (maximum at 8 ϩ ) in positive ESI mode (Fig. 5C), which is similar to that observed for wild-type V. harveyi ACP (34). CycL46W, on the other hand, produced a sharp, narrow CSD of predominantly 6 ϩ and 7 ϩ ions (Fig.…”
Section: Resultssupporting
confidence: 75%
“…However, of particular interest here is the difference in charge state distribution (CSD) of cycL46W and linL46W. We recently reported that V. harveyi ACP exhibits a similar broad CSD regardless of its conformation in solution, as manipulated by charge neutralization or fatty acylation (34). We further speculated that ACP may unfold rapidly upon entering the gas phase during ionization, unlike many other proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…So, the acetylation did not cause unfolding of the protein, and did not affect the average charge state of the protein in the gas phase [38,39]. Closer inspection of the EIEs shows a consistent sub-peak in front of the main peaks.…”
Section: Ce-ms Of Basic Proteinsmentioning
confidence: 85%
“…Conformational effects are, thus, at the basis of the most dramatic changes in CSDs and are quite universal. There is only one reported case, Vibrio harveyi acyl carrier protein, showing no spectral changes under conditions known to modulate protein conformational properties in solution (Murphy, Rowland, & Byers, 2007). Further experiments will be needed to explain the observed behavior.…”
Section: Introductionmentioning
confidence: 96%